2021
DOI: 10.1149/2162-8777/abe093
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Recovery of Silicon Photovoltaic Cells by Application of an Organic Solvent Method

Abstract: The treatment of photovoltaic (PV) waste is gaining traction the world over, with the recovery of valuable materials from end-of-life, or damaged and out-of-spec polycrystalline silicon PV modules. These materials are a focus of recycling. However, the current recycling practices usually involve excessive damage to PV cells that could otherwise be reused if extracted undamaged. The ability to extract undamaged PV cells, capable of reuse, would serve to further reduce the carbon footprint and cost associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The efficacy of pure hexane in dissolving EVA has been demonstrated. Furthermore, X-ray diffraction (XRD) analysis has indicated that hexane does not cause damage to the front surface of photovoltaic cells [36]. The utilization of trichloroethylene in conjunction with microwave recycling of EOL solar panels has been found to accelerate the separation of distinct layers.…”
Section: Chemical Delaminationmentioning
confidence: 99%
“…The efficacy of pure hexane in dissolving EVA has been demonstrated. Furthermore, X-ray diffraction (XRD) analysis has indicated that hexane does not cause damage to the front surface of photovoltaic cells [36]. The utilization of trichloroethylene in conjunction with microwave recycling of EOL solar panels has been found to accelerate the separation of distinct layers.…”
Section: Chemical Delaminationmentioning
confidence: 99%
“…However, aluminum has the potential to form compounds with silicon in sulfuric acid. silver is expected to form AgCl precipitate in hydrochloric acid [17]. In addition, the copper and lead contained in the PV ribbon are not oxidized in sulfuric acid [18] and are reported to be soluble in nitric acid [19,20] and hydrochloric acid [21].…”
Section: Selective Leachingmentioning
confidence: 99%
“…In addition, the copper and lead contained in the PV ribbon are not oxidized in sulfuric acid [18] and are reported to be soluble in nitric acid [19,20] and hydrochloric acid [21]. In this study, nitric acid was used as a leaching agent based on the survey contents [17][18][19][20][21], and a method of recovering high-purity silicon and silver in the recovered solution after leaching was derived.…”
Section: Selective Leachingmentioning
confidence: 99%
“…Chemical methods can be used to recover intact module components; however, the reaction time required increases with an increase in the area of the module. Research is currently underway to solve this problem [42][43][44][45][46][47][48]. Another disadvantage of this process is the burden of additional environmental pollution generated by the treatment of used chemicals.…”
Section: Photovoltaic Module Recycling Processesmentioning
confidence: 99%
“…(3) Chemical processes use solvents or acids to dissolve and separate different materials in the PV modules, and the separated components are then processed for recycling or reuse. These processes require careful management and disposal of the chemicals used, as well as proper treatment of the wastewater generated during the process [42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%